Lack of PCSK6 Increases Flow-Mediated Outward Arterial Remodeling in Mice - Samuel Röhl; Bianca E. Suur; Mariette Lengquist; Till Seime; Kenneth Caidahl; Ulf Hedin; Anders Arner; Ljubica Matic; Anton Razuvaev (Cells, 2020)
Proprotein convertases (PCSKs) process matrix metalloproteases and cytokines, but their function in the vasculature is largely unknown. Previously, we demonstrated upregulation of PCSK6 in atherosclerotic plaques from symptomatic patients, localization to smooth muscle cells (SMCs) in the fibrous cap and positive correlations with inflammation, extracellular matrix remodeling and cytokines. Here, we hypothesize that PCSK6 could be involved in flow-mediated vascular remodeling and aim to evaluate its role in the physiology of this process using knockout mice. Pcsk6−/− and wild type mice were randomized into control and increased blood flow groups and induced in the right common carotid artery (CCA) by ligation of the left CCA. The animals underwent repeated ultrasound biomicroscopy (UBM) examinations followed by euthanization with subsequent evaluation using wire myography, transmission electron microscopy or histology. The Pcsk6−/− mice displayed a flow-mediated increase in lumen circumference over time, assessed with UBM. Wire myography revealed differences in the flow-mediated remodeling response detected as an increase in lumen circumference at optimal stretch with concomitant reduction in active tension. Furthermore, a flow-mediated reduction in expression of SMC contractile markers SMA, MYH11 and LMOD1 was seen in the Pcsk6−/− media. Absence of PCSK6 increases outward remodeling and reduces medial contractility in response to increased blood flow.